Chemically exfoliated 1T-phase transition metal dichalcogenide nanosheets for transparent antibacterial applications. (28th February 2019) - Kim, Tae In; Kim, Jayoung; Park, Ick-Joon; Cho, Kyung-Ok; Choi, Sung-Yool
Abstract: Two-dimensional transition metal dichalcogenides (TMDs) are promising materials for a range of applications owing to their intriguing properties including the excellent electrical performance and biocompatibility. Strikingly, 1T-phase TMDs have attracted significant interest based on their metallic properties with octahedral metal coordination where the phase transition can occur from the semiconducting 2H-phase to metallic 1T-phase by chemical intercalation-induced exfoliation process. In this regard, 1T-phase TMDs have great potential in antibacterial agents in terms of effective charge transfer between the bacterial membrane and TMD nanosheets while their biological interactions have been underexplored. To bridge this gap, we herein investigate the antibacterial activities of various 1T-phase TMDs including molybdenum disulfide (MoS2 ), tungsten disulfide (WS2 ), and molybdenum diselenide (MoSe2 ) toward Gram-negative bacteria Escherichia coli that exhibit the reduction of bacterial viability caused by the production of reactive oxygen species, oxidation of glutathione and other chemical functionalities. The effective antibacterial capacity of metallic 1T-phase TMDs is observed and their bactericidal mechanisms are investigated in terms of their electrical conductivity and chemical oxidation property that induce the charge transfer from bacterial membrane to TMDs leading to the continuous disruption of bacteria and loss of cellular components. Furthermore, we demonstrated the transparent antibacterial films consisting of 1T-phase TMDs in which TMD nanosheets are immobilized on the surfaces and their basal planes play an important role in antibacterial actions for practical biomedical applications. Thus, our findings provide new insights into the great potential of 1T-phase TMDs as promising building blocks for antibacterial surfaces and contribute to the widespread use of 1T-phase TMDs for practical biomedical applications.